Rare disease, common struggles: quality of life, caregiver burden and financial wellbeing of family caregivers in Poland - Jan Domaradzki; Piotr Jabkowski; Dariusz Walkowiak (Scientific Reports)
Abstract Caregivers of persons with rare diseases (RDs) face elevated stress levels, caregiver burden (CB), financial pressure, and decreased quality of life (QoL). Since the Polish Rare Diseases Plan for 2024–2025 does not address caregivers’ psychosocial needs, this study aimed to assess the experiences of Polish parents of persons with RD. A self-administered, anonymous, computer-assisted online survey was conducted between March and August 2024 to examine the relationship between parenting a person with RD and caregivers’ QoL, CB, and financial well-being. The survey included 942 Polish caregivers of individuals with RDs. The study demonstrated a statistically significant negative association between perceived CB and all dimensions of parents’ QoL – physical health, psychological health, social relationships, and environment – indicating a broad decline in QoL as CB increases. Financial well-being emerged as a consistent positive predictor of QoL and was shown to buffer the negative effects of CB, underscoring its role as a critical resource for caregivers. Additionally, CB was associated with adverse experiences related to the diagnostic odyssey and its perceived consequences. Our findings highlight that long-term caregiving for individuals with RDs imposes substantial emotional, financial, and social burdens. To effectively address these challenges, Polish health policy must move beyond the biomedical model and adopt a comprehensive approach that integrates psychological, social, and financial support for RD families. Future research should explore targeted interventions that strengthen caregiver resources and reduce systemic barriers to support.